Моделирање на хидромеханичкото однесување на незаситени почви и нестабилност на косини предизвикана од врнежи - Сусинов, Бојан (Градежен факултет, УКИМ, Скопје, 2021)
Intense rainfalls, as a result of an atmospheric impact, climate variations, and changes, are often seen as a cause for instability, landslides, or significant erosion of natural and engineering slopes. Through the infiltration of atmospheric water, the natural moisture of the material is affected, which reduces the initial suction and finally reduces the unsaturated soil shear strength. Several papers in this area indicate that this reduction in strength, most commonly expressed through the safety factor, can be significantly reduced by making stable slopes conditionally stable or unstable. Hence, it is recommended that it is necessary to include the impact of precipitation in the slope stability analysis. In the literature, this phenomenon is described as soil-atmosphere interaction. Therefore, this dissertation will present an advanced concept for slope stability analysis that takes into account the time-dependent mechanical, hydraulic, and thermal behavior of soils as a multiphase system. For its application, in addition to the usual mechanical, it is necessary to determine the hydraulic characteristics of the soil, precipitation loads, here obtained through statistical processing of measured data, as well as appropriate measuring equipment that will determine the change of key parameters that have an impact on local and global slope stability. The main goal of this doctoral dissertation is to contribute to the understanding of the hydromechanical behavior of unsaturated sandy soils and their impact on rainfall-induced slope instability through a holistic approach that combines theoretical, laboratory, experimental and numerical research. The reference material in this research is one from the tailings dam Topolnica which is part of the mine Buchim in Radovish. Standard tests show that this is a uniform material characterized as silty sand. The mechanical and hydraulic characteristics are determined in the laboratory through appropriate tests that are considered crucial in the selection of the hydraulic and constitutive models that simulate the coupled hydromechanical behavior of unsaturated soil. The determination of the relevant rainfall intensity and its duration is obtained through statistical analysis of the measured rainfall for the area for a certain probability of occurrence of maximum rainfall and its characteristic durations. To define the hydromechanical behavior of unsaturated soil, an experimental study of a large-scale physical model of an ideal slope exposed to intense rainfall was conducted. The model was instrumented with sensors to measure changes in moisture, suction, pore, and total soil pressure and deformation. The results of this study lead to a better understanding of the impact of infiltrated water on suction and the development of pore pressure. After almost 10 hours of precipitation with an intensity of 35 mm / h, the slope is completely saturated, which leads to its complete collapse. However, the most important findings from the study define the mechanism and the impacts that lead to the terminal state. It can be concluded that water filtration and suffosion, in addition to suction and pore pressure, lead to destabilization and slope failure. According to the observations obtained from the physical model, in the next step, numerical modeling of the slope was performed by using FEM. The main task of this test was to calibrate the theoretical model through previously determined values and results. For that purpose, a fully coupled flow-deformation analysis with time-dependent boundary conditions and precipitation was conducted. The advantage of numerical modeling is used to form a complete view of the development of hydromechanical variables and to establish their relationship according to Bishop's theory in defining the effective stress which involves the suction and the degree of saturation. The simplest Mohr-Coulomb law is used for mechanical modeling, and the emphasis is on the definition of the hydraulic model by applying the soil retention curve (SWRC) and the function of hydraulic conductivity as a function of suction and water permeability coefficient. Stability analysis performed by reducing the soil strength parameters shows a safety factor close to the slope equilibrium limit state, with a safety factor of 1.037. Finally, the results of the physical and numerical models are compared with each other and they successfully show the behavior of the material with great accuracy and define the degree of reliability of the slope. The results of the numerical analysis fully confirmed those of the physical model with minimal deviations from the basic parameters such as the development of deformations, pore pressure, suction, and moisture content over time. The comparative analysis makes a key contribution to improving the existing constitutive models for coupled flowdeformation analysis. All previously established findings from the model research of the ideal slope are used to analyze the stability of the Topolnica tailings dam. The results obtained, although satisfactory in terms of global stability, indicate the significant impact of infiltrated water which causes relatively rapid saturation of the material and defines potentially unstable zones which is visible through about 15% reduction of the safety factor for a given geometry. As a general conclusion, it should be noted that the obtained results confirm the initially set thesis that the role of precipitation can have a significant impact on destabilization of the surface layers at slopes where initial erosion occurs, leading to local instability which eventually ends in global fracture and landslides. It can also be concluded that the duration of precipitation and the initial degree of saturation have a significant impact, so if they change and lead to complete saturation of the surface layers of the slope, they will cause runoff water down the slope and formation of local gullies, as it was observed on the dam after heavy rainfall in the past. The results indicate that the global degree of slope safety after a critical event defined by the relevant intensity and duration of precipitation can lead to a reduction of 10% to 30% depending on the geometry and the material of the slope. In addition to the conclusions, certain recommendations are presented which, by including the effects of atmospheric influences, aim to raise the level of design of engineering slopes in the future, which will generally contribute to more stable and safer infrastructure slopes. The main contribution of this doctoral dissertation is seen in the assessment of the impact of infiltrated water on moisture, suction, and evapotranspiration which, as it was seen, have a significant impact on the slope stability exposed to heavy rainfall.
Докторска дисертација одбранета во 2021 година на Градежниот факултет во Скопје, под менторство на проф. д–р Јосиф Јосифовски.
Keywords: rainfall, slope, unsaturated soils, stability, erosion, physical model, numerical model